Benzylation of acetic acid to benzyl acetate over highly active and reusable micro/meso-HZSM-5 - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Raut, Sunil A.; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
Catalytic benzylation of acetic acid (AA) with benzyl alcohol (BA) to benzyl acetate was studied over zeolites viz. H-ZSM-5 (microporous, medium pore), Micro/Meso-HZSM-5 (combination of micro- and meso pore), H-Beta (microporous, large pore) to investigate catalytic activity and selectivity towards benzyl acetate. Micro/Meso-HZSM-5 obtained by desilication post-treatment has been employed as a heterogeneous catalyst for benzylation reaction probably for the first time. Micro/Meso-HZSM-5 was found to be a promising catalyst for benzylation with AA conversion of 94%, selectivity towards benzyl acetate of 95%. The detailed optimization of process parameters such as molar ratio, catalyst loading, reaction temperature and time was also presented. Micro/Meso-HZSM-5 catalyst was observed to be stable for six cycles (1 fresh and 5 recycles). The first order reaction kinetics (R-2 >0.98) indicated that reaction rate constants increased with increasing reaction temperature. The activation energy for benzylation of AA with BA over Micro/Meso-HZSM-5 was obtained to be 15.07 kJ mol(-1), which is far less than the reported. (C) 2014 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Acetic acid; Benzyl acetate; Benzyl alcohol; Benzylation; Micro/Meso-HZSM-5; Reaction kinetics

Estimation of reaction kinetics for aromatic and heterocycles nitration in mixed acids through computational chemistry approach - Jadhav, Pandurang M.; Pandey, Raj K.; Kulkarni, Amol A. (International Journal of Chemical Kinetics, 2021)
Nitration of aromatic compounds and heterocycles in mixed acid environment is one of the regularly performed large-scale reactions in the chemical industry. Although the reaction mechanism of nitration of aromatics in mixed acid is well established, the development of a methodology for the evaluation of kinetics of exothermic aromatic nitrations in a simplified and accurate way is necessary. Here we evaluate the applicability of a kinetic evaluation methodology based on Hammett's acidity function, acidity function, and empirical activity coefficient for the nitration reaction. The contributions from the functional groups on the aromatic ring and quantitative structure-activity relationships technique are considered for these evaluations. Natural bond orbital and magnetic index nucleus independent chemical shift analyses were carried out to obtain the substitution constants. The rate constant and activation energy values were evaluated at various temperatures and sulfuric acid strengths. The results were validated by comparing with the experimental data from the literature for several molecules. The effect of various functional groups (viz carbonyl, carboxyl, methyl, and amine) substituted on the benzene ring was also evaluated. For a few identified substrates, the data were used for estimation of residence time needed for complete conversion in continuous stirred tank reactor and in a plug flow reactor to quantify the effect of substitution constant and strength of sulfuric acid. The approach will help select a suitable reactor.
Keywords: Aromatic nitration; computational chemistry; Hammett analogy; mixed acids; Reaction kinetics; reactor selection

Quantitative understanding of nucleation and growth kinetics of silver nanowires - Patil, Suneha; Kate, Prachi R.; Deshpande, Jaydeep B.; Kulkarni, Amol A. (Chemical Engineering Journal, 2021)
We have demonstrated that using polyol synthesis, it is possible to prepare high aspect ratio silver nanowires by controlling the experiments for process related issues which are usually ignored, viz. the overhead space in the batch reactor. It is found that by controlling the presence/absence of NOx gases with refluxing of nitric acid in the batch reactor with an overhead space of 80% volume, near complete conversion (-99%) of high aspect ratio NWs (-1000) can be attained. We provide a detailed understanding of other factors assisting in rapid polyol synthesis like temperature, stirring rate, Chloride ion concentration, optimal PVP weight ratios and PVP/AgNO3 ratio that can lead to high aspect ratio NWs. Besides the process parameters and reagent concentration effects, kinetic studies based on our nucleation and R-C Model evaluate the overall reaction rate constants for silver nanowires and the JMAK approach is used to theoretically validate our experimental results of the reactor headspace having strongest effect on the aspect ratios. Our study highlights the importance of various complications in the polyol synthesis, through detailed kinetic modelling and affixes values of temperature, reactor headspace, stirring rate and residence time in order to achieve reproducible synthesis of nanowires with complete conversion along with a method to separate these nanowires.
Keywords: Conducting inks; growth; Nucleation; Reaction kinetics; Redox-crystallization; Silver Nanowires

Imine oxidation catalyzed by zinc hydroxyapatite: kinetic studies - Vishwakarma, Rakhi; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (ChemistrySelect, 2023)
The synthesis of N,N-diphenylformamide from N-benzylideneaniline and urea hydrogen peroxide is investigated using a zinc hydroxyapatite (ZnHAP) catalyst. It was found that the catalyst resulted in the highest activity of 91 % conversion and 40 % selectivity at 130 degrees C in 2 h. A kinetic model was validated by Langmuir-Hinshelwood-Hougen-Watson (LHHW) at different temperatures and the absence of mass transfer resistance was proved by the Weisz Prater criterion. Effect of different catalysts, catalyst loading, temperature, mole-ratio, and speed of stirring was studied. The as-synthesized catalyst is characterized by FTIR, BET nitrogen adsorption-desorption, TEM, EDX, TPD-NH3, XPS, ICP-MS and XRD. ZnHAP catalyst was found to be stable up to three recycles with no loss in activity.
Keywords: heterogeneous catalysis; hydroxyapatite; imines; Oxidation; Reaction kinetics

Reaction kinetics for dehydrogenation of decahydroquinoline to quinoline for hydrogen generation - Bagwan, Farahanaz M.; Dadkar, Sarthak S.; Kinage, Anil K.; Vasireddy, Satyam Naidu (Chemical Engineering & Technology, 2026)
Catalytic dehydrogenation of decahydroquinoline (DHQ) to quinoline is a promising pathway for hydrogen release in liquid organic hydrogen carrier systems. In this work, solvent-free DHQ dehydrogenation over Pd/Al2O3 is systematically investigated to evaluate hydrogen release performance and reaction kinetics. High DHQ conversion (83.9%) and degree of dehydrogenation (82.7%) are achieved at optimal reaction conditions. A power-law kinetic model based on a simplified reaction mechanism is developed and simulated using a Markov Chain Monte Carlo (MCMC) approach for estimation of rate constants and validation of concentration profiles with experimental data. The apparent activation energies are determined to be 45.85 kJ/mol for DHQ to 5,6,7,8-tetrahydroquinoline (bz-THQ) and 185.43 kJ/mol for bz-THQ to quinoline formation, identifying latter as the rate-limiting step. This framework provides mechanistic insight and supports the potential of DHQ as an efficient hydrogen carrier.
Keywords: Decahydroquinoline (DHQ); degree of dehydrogenation; Dehydrogenation; rate-limiting step; Reaction kinetics; Weisz-Prater criterion